ANALISIS KEBUTUHAN TENAGA DOKTER UMUM DI UNIT GAWAT DARURAT RS ISLAM PKU MUHAMMADIYAH PADA TAHUN 2018 - Nurmala Dewi; Dian Megasari Pattimahu (Universitas Khairun, 2019)
There is no special rules in Indonesia that organize about office hours of medical doctor that cause doctor often work more than they have to. In North Maluku as known as Ternate, especially in Islamic Hospital, the number of medical doctor is very low than other hospital, besides Islamic Hospital is one of the highest visiting patient in North Maluku. There are a lot of rumour in people nowadays that the service of these hospital especially in Emergency Room was took too long and sometimes the patients family had to complain first before they got treatment from doctor. It may cause by unbalanced between amount of medical patient who visited and total of onduty doctor and it maybe even worsening with massive office hours. The study methode was Descriptive. The sample of this study were the office hour and the shift. The result of this study show that General Practitoner in Emergency Room at Islamic Hospital Ternate hace office hour more than they had to. In fact, these condition can effect their quality of work and unfortunately, their health.